Seasonal variation in heavy metal concentrations in sediment from Khalasi Estuary, Hormozgan, Iran - Razaghi, M.; Taherizadh, M. R.; Mashjoor, S. (Indian Journal of Fisheries, 2018)
The study aimed for a preliminary assessment of the distribution and levels of five heavy metals (Zn, Cu, Pb, Fe and Ni) in surface sediment of Khalasi Estuary, Hormozgan, Iran, collected from three stations during four seasons of the year, 2012-2013. The estuary does not receive domestic and industrial untreated wastewaters. The range of metal concentrations (mg g-1 dw) recorded were: Zn 0.051-0.164; Cu 0.016-0.061; Pb 0.001-0.460; Fe 2.541-6.537 and Ni 0.019-0.131. The spatial variation in concentrations and comparison among seasons indicated that there are significant differences in the concentrations of metals in sediment for all seasons. The results of correlation analyses showed that there is significant positive correlation for Fe-Total Phosphorus, Ni-Total Organic Matter, and Zn-Total Organic Matter and also significant positive correlation between levels of lead, copper and zinc metals with that of levels of silt and clay in the sediment. According to the guideline values, the concentrations of metals studied do not pose a threat to the ecology of the area.